Lamprey IGF-Binding Protein-3 Has IGF-Dependent and -Independent Actions - Zhong, Yingbin; Duan, Cunming (Frontiers in Endocrinology, 2017)
Insulin-like growth factor-binding proteins (IGFBPs) are multifunctional proteins that possess IGF-dependent and -independent actions. Recent studies suggest that its IGF-independent action appeared early and that the IGF-binding function may have been acquired later in evolution. The timing of the emergence of IGF-dependent actions is unclear. Here, we identified and characterized an igfbp gene from sea lamprey, an agnathan, which was separated from the jawed vertebrates 450 million years ago. Phylogenetic and structural analyses suggested that the encoded protein belongs to the IGFBP-3 clade in the IGFBP family. Lamprey IGFBP-3 contains an IGF-binding domain (IBD), nuclear localization signal, and transactivation (TA) domain. Biochemical and functional analyses showed that these domains are all functional. Lamprey IGFBP-3 can bind IGFs and modulate IGF signaling when tested in mammalian cells. Lamprey IGFBP-3 also has the capacity to enter the nucleus and has strong TA activity. Forced expression of lamprey IGFBP-3, but not its IBD mutant, in zebrafish embryos decreased body growth and developmental speed. Lamprey IGFBP-3 inhibited BMP2 signaling in cultured cells and in zebrafish embryos, and this action is independent of its IGF-binding function. These results suggest that lamprey IGFBP-3 has both IGF-dependent and -independent actions and provide new insights into the functional evolution of the IGFBP family.